IMPLEMENTASI PERATURAN DAERAH NOMOR 11 TAHUN 2000 TENTANG PENGATURAN DAN PEMBINAAN PEDAGANG KAKI LIMA TERHADAP KETERTIBAN PEDAGANG KAKI LIMA DI KOTA SEMARANG - Rubiyanto S.H., M.H. (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2012)
In the framework of the arrangement of the street hawkers in the city of Semarang, Semarang Municipality normatively has issued the Local Regulation No. 11 of Semarang City 2000 on the Regulation and Development of the street hawkers. This research used an empirical legal research and the analytical desriptive. The Implementation of the Regional Regulation No. 11 of 2000 on Regulation and Development of the street hawkers, technically made by the Office of Semarang City Market on duty and authorized to regulate the presence of street hawkers in all areas of Semarang. In the field implementation is coordinated by the Office of the District and the Subdistrict Office. The obstacles encountered in the implementation of the Regional Regulation No. 11 of 2000 on Regulation and Development of the street hawkers in Semarang, viz : lack of legal awareness, lack of supervision by the law enforcement officers, relocation, unadequate strategic, and economical factors.